Mesa Redonda: Felicidad y Educación Legal - Schudson, Charles (2014)
In recent decades, a series of studies have demonstrated that lawyers present   high suicide, alcoholism and divorce rates, even higher than those corresponding  to other professionals. Law students and lawyers are now ranking highest in all of this statistics.It’s on that basis, and considering that the search for wellness is fundamental for every person’s health, the rapporteurs expose the relation between happiness and legal education nowadays, concluding that it is necessary to reconsider the way in which Lawis taught in today’s world.